The Centrifugal Differential Mobility Analyser – concept and initial validation of a new device for measuring 2D property distributions - T. N. Rüther; D. B. Rasche; D. B. Rasche; H.-J. Schmid (Aerosol Research)
Usually for the characterization of nanoparticles, an equivalent property is measured, e.g. the mobility-equivalent diameter. In the case of non-spherical, complex-shaped nanoparticles, one equivalent particle size is not sufficient for a complete characterization. Most of the methods utilized to gain deeper insight into the morphology of nanoparticles are very time-consuming and costly or have bad statistics (such as tandem setups or TEM (transmission electron microscopy)/SEM (scanning electron microscopy) images). To overcome these disadvantages, a prototype of a new compact device, the Centrifugal Differential Mobility Analyser (CDMA), was built, which can measure the full 2D distribution of mobility-equivalent and Stokes equivalent diameters by classification in a cylinder gap through electrical and centrifugal forces. An evaluation method to determine the transfer probabilities is developed and used in this work to compare the measurement results with the theory for the pure rotational behaviour (like the Aerodynamic Aerosol Classifier) and the pure electrical behaviour (like the Dynamic Mobility Analyser). In addition, the ideal 2D transfer function was derived using a particle trajectory approach. This 2D transfer function is a prerequisite for obtaining the full 2D particle size distribution from measurements by inversion.